Benefits of physical activity in the prevention and treatment of obesity: A brief review (Research, Society and Development, 2021)
The objective of the present work is to evaluate the benefits of physical activity in the prevention and treatment of obesity. Only national searches were carried out by, academic Google, LILACS and Scielo with the next years of publication from 2006 to 2018 using the words physical activity, physical exercise or physical training, aerobic exercise, resistance exercise or weight training and obesity researched individually and jointly as obesity, which provide for tracking articles and monographs in pdf formats, which were verified by the literature review method. In view of all the studies generated, what can be observed is that the practice of physical activity promotes an improvement in the reduction of body fat through aerobic or resistance training through exercises such as: walking, running, and cycling, weight training, among others. Therefore, a survey conducted through the method of literature review on physical activity and obesity concluded that most articles and monographs that have been affected beneficial effects of physical activity in obese people. Because the literature shows that in addition to physical activity to help reduce body fat it also helps to reduce the risks of diseases associated with it.